2010
DOI: 10.1007/s10897-010-9289-x
|View full text |Cite
|
Sign up to set email alerts
|

What Do Genetic Counselors Learn on the Job? A Qualitative Assessment of Professional Development Outcomes

Abstract: Professional development is an important goal for professionals in human service fields such as counseling, teaching, and nursing. However, there are relatively few published papers on this topic specific to genetic counselors, and no studies systematically examine the outcomes of their professional development. This study was designed to investigate genetic counselors' perceptions of their post-degree learning and to compare themes in their learning to those of psychotherapist professional development models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…The present findings are consistent with Runyon et al’s () findings of what genetic counselors learned on the job. Their participants similarly noted difficulties with confidence as a new professional and needing to become comfortable with not knowing everything.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present findings are consistent with Runyon et al’s () findings of what genetic counselors learned on the job. Their participants similarly noted difficulties with confidence as a new professional and needing to become comfortable with not knowing everything.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, they encouraged new graduates to seek support and advice from others, no matter how small or simple a question/issue may seem. Their recommendations are congruent with advice offered by genetic counselors in the Runyon et al () study, namely, practicing self‐care, managing self‐expectations, recognizing one's limits, and seeking help/mentorship as needed.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The correct responses varied between 70 and 89 % across the four scenarios. Yet, regardless of recent graduates' actual ability to interpret results, their perceptions may hinder their inclination to become involved in PGT in the future (Runyon et al 2010). Therefore, results of this study suggest that although recent graduates believe genetic counselors will play a role in interpreting PGT results in the future, further training is indicated in order to help genetic counselors feel more prepared to provide this service.…”
Section: Future Rolesmentioning
confidence: 82%
“…In general, fewer challenges in this study were reported by genetic counsellors who had experience working as a genetic counsellor before they entered private practice. Previous research has demonstrated that professional development and working experience help genetic counsellors to expand their knowledge, build skills, and gain confidence in their judgement (Callanan and Grosse 2016;Runyon et al 2010;Zahm et al 2016). Stronger connections built over time with professional colleagues also contribute to the ability of some genetic counsellors to better manage challenging events (Zahm et al 2016).…”
Section: Discussionmentioning
confidence: 99%